Brazil and the TPNW: Brazilian Interests and the Promotion of the Norm of Nuclear Prohibition - Luiza Elena Januário; Raquel Gontijo (Contexto Internacional)
Abstract The Treaty on the Prohibition of Nuclear Weapons (TPNW) formalises the norm of nuclear prohibition and is presented as a way to fill a gap regarding nuclear disarmament. Brazil played a leading role in the negotiation of this treaty, in line with its historical advocacy for disarmament. This article aims to analyse the foundations of the Brazilian position, guided by the following question: Can Brazil be considered a norm entrepreneur in favour of the prohibition of nuclear weapons? We hypothesise that Brazil has not truly solidified its role as a normative entrepreneur, exhibiting an ambiguous stance. We begin the article with a discussion of the contributions of norm constructivism. Next, we present some elements of the nuclear normative order. Finally, we analyse Brazil’s posture regarding TPNW and the norm of nuclear prohibition. We provide a historical reconstruction of Brazil’s position, situating it in the context of the norm cluster around nuclear weapons. Despite being vocal in advocating for disarmament, we conclude that Brazil has not fully established itself as a norm entrepreneur in promoting the norm of nuclear prohibition and presents an ambiguous stance due to its weak adherence to humanitarian motivation as the foundation of this norm.